The non-Thomistic Character of Aristotle’s (and Thomas’s) Ethics - Taccolini, Joshua (Conatus - Journal of Philosophy, 2025)
Even today, some Thomists follow the Early Modern, Neo-Scholastic tradition in reading Thomas Aquinas’s ethics as an Aristotelian, reason-dominant model in which emotions play a secondary role in the virtuous life. The virtuous person is one for whom reason is superior to and rules over the emotions. Alternatively, Eleonore Stump dissociates Thomas Aquinas’s ethics from Aristotle in an effort to overcome intellectualist interpretation. In this paper, I draw on Eugene Garver’s Aristotle scholarship to offer a reading of Aristotle’s ethics free of its Neoplatonic intellectualist reception in the Thomistic Commentary tradition. In doing so, I support Thomists who see emotivist elements in Thomas Aquinas’s ethics but do not yet see them in Aristotle. For these Thomists, Thomas Aquinas’s ethics will turn out, once again, Aristotelian.